Kinematic analysis of elite male tennis player's step movement for return of service - Li, Y.; Zhou, J. (ISBS - Conference Proceedings Archive (Konstanz), 2013)
A three-dimensional camera analytic method was used to make kinematic analysis on three players' step movement for return of service in finals and semi-finals of the ATP Champions Tour. The movements were broke down to three stages (preparation stage, skip step stage, stroke stage) for analyzing the kinetic parameters. Then the kinematic characteristics of elite tennis player`s step movement for return of service were derived, to serve as reference for skill training and tennis matches. It was found that: in the preparation stage, Sampres, Aynaoui and Moya have an average horizontal angle between the feet of 12.1deg., 2.2deg., 45.6deg.respectively. In the stroke stage, the travel distances of Sampras and Moya were found to be greatly differed (0.892m and 0.667m respectively), and move faster (2.23m/s and 1.96m/s respectively).